MAIN PECULIARITIES OF PROJECT-BASED LEARNING IN ENCOURAGING LANGUAGE SKILLS PERFORMANCE (Web of Teachers: Inderscience Research, 2024)
Meaningful learning should bring learners to meet their entire goals-both an achievement in academic skills and everyday life skills. This current article focused on the implementation of project-based learning (PBL) in language learning classroom. The investigation aimed at the development of students’ performance in learned language. The study also found that PBL played the role in the enhancement of language learning skills improvement. Majority of participants mentioned that project-based activity engaged them to develop collaboration and teamwork skills, flexibility and adaptability skills and increased the better level of responsibility in learning.